Tingkat Pengetahuan Ibu Primigravida Berhubungan dengan Kecemasan Rencana Sectio Caesarea - Nindya Saputri; Sondang R. Sianturi (STIKes Panti Rapih, 2020)
Background: Every pregnant women desire to normal childbirth, but under certain conditions it is necessary to have a Caesarean section delivery. The process of giving birth to a Caesarean section will cause anxiety and fear because of the lack of information obtained by the mother regarding the section caesarean procedure to be performed. Objective: The purpose is to describe the relationship between knowledge level and anxiety level of primigravida mothers with caesarean section plan. Methods: Type of this research is correlational study with a cross sectional design using the Kendal tau test analysis. This research was conducted at X hospital in Bekasi. The sampling technique was purposive sampling, with 30 primigravida mothers with term pregnancy, no complications to the mother and will perform a caesarean section. Result: The results of univariate analysis are 96.7% of respondents aged 20-35 years, 53.3% have a college education background, 46.6% as enterpreneurs, 36.7% of respondents have sufficient knowledge with 63.3% have support family, 70% received support from health workers, and 40% of respondents’ experienced moderate anxiety and 20% had severe anxiety. Based on the results of the bivariate analysis, it was found that there was a relationship between education (pvalue 0.015), work (pvalue 0.019), family support (pvalue 0.016), and support from health workers (pvalue 0.001) on anxiety, and there was a relationship between knowledge and anxiety of respondents with pvalue 0.002. But there is no relationship between age and respondent anxiety with a pvalue of 0.297. Conclusion: From the results of statistical tests in this study, it was found that there was a significant relationship between the respondent’s level of knowledge and anxiety experienced in dealing with caesarean section delivery.